Media Sosial Untuk Usaha Mandiri Pada Masa Pandemik Di Yayasan Baitul Karim - Eko Suharyanto; Chrisantus Tristianto; Imam Hidayat; Yunus Yunus (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
Today's technological advances can take advantage of the internet and their mobile devices to develop online businesses so that they can drive a wider market. The implementation of this PKM is carried out, with 1) The purpose of training for the Baitul Karim Foundation community. 2) Train the Baitul Karim Foundation community to use this social media by selling online. One of the platforms is the Tokopedia seller, one of the features found in the Tokopedia company that functions as a supporter of business actors to facilitate product marketing throughout the archipelago. As for how to register our account on Tokopedia, Tokopedia has advantages in the components of reviews and complaints (UK), certification and security (SK), product prices (HP), product descriptions (DP), and transportation (TR). This gives enthusiasm to provide workshops to several sellers or sellers by selling online through social media and several platforms such as Facebook, Instagram at the Baitul Karim Foundation.